Low-latitude glaciation in the Neoproterozoic of Oman - Kilner, B; Mac Niocaill, C; Brasier, M (2005)
Although Earth is widely believed to have undergone a series of extreme low-latitude snowball glaciations during the Neoproterozoic (ca. 1000-543 Ma), only one reliable paleomagnetic result, from Elatina, South Australia, places glacial rocks close to the equator. We report new paleomagnetic data from the Neoproterozoic Huqf Supergroup of Oman that pass fold and reversal tests and yield a paleopole at 52.3°S, 074.4°E (N = 25 sites; α95 = 7.3°). This paleopole places the Muscat region of Oman at a latitude of 13° in the late Neoproterozoic and provides the first direct evidence that both glacial and overlying cap carbonate units were deposited in the tropics. The presence of glacial-interglacial cyclicity within the Huqf Supergroup indicates that areas close to the equator may have been largely free of ice at the time of deposition, a result that is inconsistent with the classic snowball Earth model. Our result precludes the possibility that contrasting lithologies mark a phase of rapid plate motion and provides the first evidence for low-latitude glaciation in Arabia. A series of magnetic reversals in the Fiq tillite and the overlying Hadash dolomite, in northern and central Oman, correlates well with a similar sequence in the Mirbat Formation in southern Oman and indicates that recovery from glacial conditions took place over long time scales (possibly >105-106 yr). © 2005 Geological Society of America.